Formation of Youth Groups Concerned about Stunting and Prevention of Early Marriage - Sholihat, Suci; Wahyuni , Elly; Burhan, Rialike (Aktual: Jurnal Pengabdian Kepada Masyarakat, 2024)
Information obtained from BPS Bengkulu Province (2018), Seluma Regency with the highest percentage of early marriage cases was found to be 30.83 percent. The cause of the high rate of early marriage is the lack of economic problems, followed by the influence of peers, family, and pregnancy out of wedlock. The purpose of this service is to increase the knowledge of the adolescent community about stunting and early marriage. The methods used in this service activity are pre-test, counseling, and post-test methods. The instruments used in this activity are questionnaire sheets and leaflet sheets. The result obtained from this service activity is an increase in knowledge of youth groups in Tumbuan Village, Lubuk Sandi District, Seluma Regency with an average increase of 5.6%. So it can be concluded that adolescent knowledge related to stunting and early marriage is increasing and involving adolescents in stunting prevention efforts and early marriage is the right choice.